2019
DOI: 10.1038/s41419-019-1806-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-bio interactions: a neutrophil-centric view

Abstract: Neutrophils are key components of the innate arm of the immune system and represent the frontline of host defense against intruding pathogens. However, neutrophils can also cause damage to the host. Nanomaterials are being developed for a multitude of different purposes and these minute materials may find their way into the body through deliberate or inadvertent exposure; understanding nanomaterial interactions with the immune system is therefore of critical importance. However, whereas numerous studies have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 137 publications
1
68
0
Order By: Relevance
“…[ 50 ] The binding of fibrinogen and other coagulation factors has been correlated with uptake by neutrophils and their subsequent activation, with an inflammatory response. [ 51 ] Interestingly, the only differences amongst the particles (Table S2, Supporting Information) included proteins, like carboxypeptidase, commonly found in the protein corona surrounding silica particles. [ 52 ] These results were mirrored by the proteic composition of the supernatants, both in comparison with the relative NPs and between each other (Figures S8–S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 50 ] The binding of fibrinogen and other coagulation factors has been correlated with uptake by neutrophils and their subsequent activation, with an inflammatory response. [ 51 ] Interestingly, the only differences amongst the particles (Table S2, Supporting Information) included proteins, like carboxypeptidase, commonly found in the protein corona surrounding silica particles. [ 52 ] These results were mirrored by the proteic composition of the supernatants, both in comparison with the relative NPs and between each other (Figures S8–S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…particle size, shape, charge, surface chemistry and aggregation), the use of in vitro models is especially appealing as they offer high-throughput and rapid testing solutions for the assessment of NM toxicity. In spite of their pivotal role in inflammation, research dedicated to the neutrophil response to NMs in vitro is relatively sparse in contrast with other cell types such as macrophages (Johnston et al 2018;Keshavan et al 2019). Working with neutrophil-like cell lines can address many of the challenges surrounding the use of human primary neutrophils (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neutrophils release neutrophil extracellular traps (NETs) in response to infection by which they capture and kill pathogens extracellularly. [181] These NETs, composed of chromatin fibers mixed with antimicrobial peptides and enzymes, are rapidly formed (<20 min) once the host is infected and have been shown to trap NPs, posing potentially a significant barrier in NP-based drug delivery. [182,183] Some studies have also suggested that NPs themselves can trigger NET formation, [183,184] as neutrophils are involved in NPs clearance.…”
Section: Future Research Challenges and Perspectivementioning
confidence: 99%